Down Syndrome: Neuropsychological Phenotype across the Lifespan - Margaret Pulsifer (MDPI AG, 2021)
Down syndrome (DS), caused by triplication of chromosome 21, is the most common genetic cause of intellectual disability (ID), with an estimated incidence of one in 700 live births [...]